The caregiver perspective: an assistive AAL platform - Costa, Ângelo (2014)
The Ambient Assisted Living area has spawned several projects that aim to help the user on his/her daily activities. The AAL4ALL (ambient assisted living for all) project aims to develop a unified ecosystem using fully compatible devices and services. The UserAccess platform is part of the AAL4ALL and has as a goal to provide assistance to a type of actor that is commonly forgotten in the Ambient Assisted Living area, the caregiver. This paper presents the archi-tecture, implementation, and interfaces, along with a brief analysis of caregiver’s needs and work related issues.